Towards a Strategic EU-NATO Security Partnership in Africa - Marsili, M. (Thinking the European Security and Defense Identity, 2021)
Threats from Africa undermine the security of Europe. The European Union and NATO have 22 member countries in common, namely most of EU member states. The fundamental role of the Atlantic Alliance is to safeguard the freedom and security of its member countries by political and military means. Since the fall of the Berlin Wall, non-state actors and hybrid threats emerged as the major challenges to international security. NATO is evolving in response to new strategic reality, and terrorism and weak states are among the most pressing challenges the Alliance faces. NATO is playing an increasingly important role in crisis management and peacekeeping. Since the African Union was established in 2001 as the successor to the Organization of African Unity, it faces difficulties in achieving the African ownership in peace and security. The chronic lack of funding and of appropriate military resources, makes the African Union depending on external aid – NATO provides military support, while the EU provides money. NATO cooperates with the AU since 2005, and all NATO-AU activities are coordinated with the EU. The NATO-EU partnership is complementar and mutual, and is based on common values and strategic interests, and should be strengthened to secure the European southern border, and to guarantee security in the Mediterranean region. Therefore, stronger and permanent NATO-EU partnership in Africa would be desirable. This brief paper investigates the ties between these three organizations, and suggests some recommendations to improve the 'trilateral' relationship to ensure security to their member states.